IMPLEMENTASI PENDIDIKAN HAK ASASI MANUSIA DI PROGRAM STUDI PPKN IKIP PGRI PONTIANAK - Hemafitria Hemafitria; Rohani Rohani (Universitas Muria Kudus, 2021)
The purpose of this study is to describe and examine the implementation of human rights education in the PPKn IKIP PGRI Pontianak study program.The research method used is qualitative with a descriptive form. The participants in this study consisted of lecturers who teach Civics courses, lecturers of Human Rights Education courses, Head of Civics Study Program and students of Civics Study Program. The data collection techniques in this study were in the form of observation techniques, interview techniques and documentary study techniques. The data collection tools used in this research are observation guide, interview guide and documentation. The data analysis technique used in this study was carried out by collecting data, reducing data, presenting data and making conclusions.The results showed that the implementation of human rights education in the Civics Study program went well. This condition was seen from the mutual respect and respect between lecturers and students, and there was no discrimination between lecturers and students. The implementation of human rights education in lectures is carried out by lecturers through strengthening students with an understanding of how important it is to respect and respect other human rights. There are several strategies in learning human rights in order to achieve the objectives, namely preparing learning such as formulating learning objectives, knowing the characteristics of students, compiling learning materials, understanding learning situations and contexts, determining appropriate learning resources, determining time and choosing appropriate learning methods. There are two factors that can affect the implementation of human rights education, namely internal factors and external factors.